Amyloid is associated with accelerated atrophy in cognitively unimpaired individuals - Henry Gilreath Stephenson; Tobey J. Betthauser; Rebecca Langhough; Erin Jonaitis; Lianlian Du; Carol Van Hulle; Gwendlyn Kollmorgen; Clara Quijano‐Rubio; Nathaniel A. Chin; Ozioma C. Okonkwo; Cynthia M. Carlsson; Sanjay Asthana; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION This study examined the association of longitudinal atrophy with baseline cerebrospinal fluid (CSF) amyloid beta (Aβ, A) and phosphorylated tau (p‐tau, T) biomarkers (Aβ42/40, p‐tau181) in 406 cognitively unimpaired (CU) individuals (6.670 years of follow‐up on average, up to 13 imaging visits) to assess whether A+ is associated with Alzheimer's disease–like atrophy and whether this depends on p‐tau181 levels. METHODS An A‐T‐ CU group free from abnormal neurodegeneration (N) was identified using a robust normative approach and used to model normal age‐related atrophy via z‐scoring. Linear mixed‐effects models tested differences in longitudinal atrophy between A+ and A‐T‐N‐ individuals and between A/T subgroups. RESULTS A+ was associated with worse atrophy within and beyond the medial temporal lobe, even at low levels of p‐tau181. DISCUSSION Neurodegeneration likely begins soon after the onset of abnormal Aβ pathology. Clinical intervention at the earliest signs of Aβ pathology may be needed to mitigate further neurodegeneration. Highlights An A‐T‐N‐ control group was identified using a robust normative approach A+ was associated with accelerated atrophy in cognitively unimpaired individuals Atrophy was observed even at low p‐tau181 levels